Enhancing Marketing Outcomes with Innovative Indigenous Products: A Case Study of Smes Supported By P3ud in Deli Serdang, North Sumatra - Lubis, Nurul Wardani; Rini, Endang Sulistya; Lumbanraja, Prihatin; Sembiring, Beby Karina F (Journal of Ecohumanism, 2024)
The primary aim of this study was to empirically examine the contribution of the Innovative Indigenous Product (IIP) approach in enhancing the marketing performance of MSMEs supported by P3UD in Deli Serdang District, North Sumatra. Through the distribution of questionnaires to 98 MSME participants and the application of Smart-PLS 3.0 for analysis, the results reveal that IIP significantly contributes to the relationship between market orientation and marketing performance, suggesting that market orientation indirectly influences marketing performance by fostering IIP. These findings highlight the importance for MSMEs to explore innovative products and services rooted in local culture, which not only boosts marketing performance but also fosters sustainable competitiveness. Additionally, the results suggest that government support plays a critical role in shaping the relationship between market orientation and marketing performance. Overall, the mediation and moderation effects underscore the significance of contingency factors as indispensable elements in efforts to enhance marketing performance.